Association of haplotypes for SNPs in the LTR regions of bovine leukemia virus with hematological indices of cattle - N. V. Blazhko; S. Kh. Vyshegurov; A. S. Donchenko; K. S. Shatokhin; T. I. Krytsyna; V. A. Ryabinina (Вавиловский журнал генетики и селекции)
Molecular typing of BLV samples isolated from Holsteinized Russian Black Pied cattle was carried out, and various cytofluorometric and morphological blood indices were examined. We performed the total count of white blood cells (WBC), lymphocyte (lymf), granulocyte (gran), monocyte (mon), red blood cell (RBC), hemoglobin (HGB), hematocrit (HTC), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red blood cell distribution width (RDW), platelet count (PLT), mean platelet volume (MPV), platelet distribution width (PDW), and platelet crit count (PCT). The LTR-region of BLV was haplotyped. Only viruses of haplotypes I (0.33±0.03) and III (0.67±0.03) of the eight possible were detected. The ratio of hematologically sick, healthy, and suspected carriers of BLV of haplotypes I and II was comparable with the results of other researchers. The numbers of leukocytes, erythrocytes and platelets in the blood of carriers of haplotype III exceeded the corresponding parameters of cattle affected by the virus of haplotype I. It is interesting to note that the difference in the hemolytic status of animals was manifested not only by the concentration of leukocytes as direct immune agents but also by the count of erythrocytes and platelets, which are not directly involved in the immune response. The number of particles of haplotype III of the BLV circulating in the blood of infected individuals exceeded that of the carriers of haplotype I. In this connection, an assumption was made about the evolutionary advantage of the more virulent haplotype III. However, the results of our own research in conjunction with the data of other scientists indicate that the high virulence of individual virus strains is a consequence of the tendency to implement the maximum possible intensity of the synthesis of virus particles but not of the high damaging effect alone. It is shown that high lethality is evolutionarily disadvantageous for viruses, since the extinction of the carrier as a biological species is fraught with the disappearance of the virus itself.